Antiparasitic Activities of Acyl Hydrazones from Cinnamaldehydes and Structurally Related Fragrances - Ibrahim S. Al Nasr; Waleed S. Koko; Tariq A. Khan; Rainer Schobert; Bernhard Biersack (Antibiotics)
Background: New drugs for the treatment of protozoal parasite infections such as toxoplasmosis and leishmaniasis are required. Cinnamaldehyde and its derivatives appear to be promising antiparasitic drug candidates. Methods: Acyl hydrazones of cinnamaldehyde, 4-dimethylaminocinnamaldehyde, and of the synthetic fragrances silvialTM and florhydralTM were prepared and tested for activity against Toxoplasma gondii (T. gondii) and Leishmania major (L. major) parasites. Results: Three cinnamaldehyde acyl hydrazones (3-hydroxy-2-naphthoyl 2a and the salicyloyls 2c and 2d) showed good activity against T. gondii, and two compounds derived from cinnamaldehyde and florhydralTM (3-hydroxy-2-naphthoyls 2a and 4a) exhibited moderate activity against L. major promastigotes. Conclusions: In particular, the identified antitoxoplasmal activities are promising and might lead to the development of new potent and cost-effective drug candidates for the therapy of toxoplasmosis.